Menopause symptoms in women and its relation with using complementary and alternative medicines: A survey in southeast Iran - Dehghan, Mahlagha; Isari, Zahra; Abbaszadeh, Mohammad Hossein; Ghonchehpour, Asma (Frontiers in Public Health, 2022)
Background Postmenopausal women are interested in using complementary and alternative medicine because of their menopausal symptoms and the side effects of chemical medications and hormone therapy. Therefore, this study aimed to investigate the relationship between the use of complementary medicine (CAM) and menopausal symptoms among postmenopausal women. Methods This cross-sectional study was conducted among 288 postmenopausal women who were referred to health centers in Kerman, southeastern Iran, from 2020 to 2021. Data were collected using a demographic questionnaire, the CAM questionnaire, and the Menopause Rating Scale (MRS). Results The mean score for the menopausal symptoms of the participants was 8.73 ± 6.11. Only 28.8% of the participants had no/little symptoms. About 65.3% of the participants used at least one type of CAM in the previous year. The most commonly used types of CAM were nutritional supplements, prayer, and medicinal herbs. A significant association was found between the use of medicinal herbs, dry cupping, relaxation and meditation, prayer, and menopausal symptoms. Women experiencing menopausal symptoms used more CAM methods than those without menopausal symptoms (Odds ratio = 2.25, 95% confidence interval = 1.33–3.80). Conclusion The study results indicated that the severity of menopausal symptoms and scores in somatic-vegetative and urogenital domains were higher in CAM users compared to non-CAM users. But there was no significant difference in the psychological domain between CAM and non-CAM users. Based on the results, it is suggested that more research be done in different communities with different healthcare systems to find out how complementary and alternative medicine affects menopausal symptoms in women.